Mid-infrared quantum cascade lasers - Chen, Tuoyang (Nanyang Technological University, 2021)
Because the operating wavelength of quantum cascade lasers (QCL) can cover Mid-infrared to terahertz wavelengths, they have a wide range of applications in the fields of Astronomical research, remote chemical sensing, security surveillance, secret military weapons detection, spectroscopy, and free space communication. Since its introduction in 1994, quantum cascade lasers have evolved from the initial laboratory principle devices to the most promising semiconductor lasers in the infrared band for practical use. In this dissertation, after describing some important theories involved in QCL, the manufacturing processes of two types of QCLs, Ridge QCL and Slot QCL, are described in detail. A typical light intensity-current-voltage (LIV) curve of ridge cavity QCL was achieved. By applying the improved structure of two isolated facet phase sections, the slot QCL realized a single-mode tuning around 10 μm with good Side Mode Suppression Ratio (SMSR) at room temperature. Finally, the contents of this paper are summarized, and future research is anticipated. Keywords: Mid Infrared, Quantum Cascade Laser, Ridge QCL, Slot QCL